Perancangan Alat Bantu Pengemasan Kompos Hijau Padat pada Green House Universitas Telkom Menggunakan Metode Ergonomic Function Deployment (EFD) Untuk Menurunkan Risiko Musculoskeletal Disorders (MSDs) - Budimansyah, Arief; Martini, Sri; Mufidah, Ilma (Innovative: Journal Of Social Science Research, 2024)
Inorganic fertilizers are often used by Indonesian people because their impacts are quickly visible. However, recently the negative impacts have begun to be felt, so many have switched to organic fertilizers. To support this transition, the production of organic fertilizers is important. Telkom University has a green house that produces compost from daily leaf waste. However, the compost production process is still manual and less ergonomic, causing workers to be at risk of Musculoskeletal Disorders (MSDs). This study aims to design a packaging aid using the Ergonomic Function Deployment (EFD) method, so that the tool is in accordance with ergonomic principles and increases production efficiency. The result is the design of a screw conveyor machine, work table, and chair. This aid has succeeded in reducing the Rapid Upper Limb Analysis (RULA) value from 6 to 2, and accelerating the packaging filling time from 55 seconds to 4 seconds.